2017
DOI: 10.1128/aem.00709-17
|View full text |Cite
|
Sign up to set email alerts
|

RpoN (σ 54 ) Is Required for Floc Formation but Not for Extracellular Polysaccharide Biosynthesis in a Floc-Forming Aquincola tertiaricarbonis Strain

Abstract: Some bacteria are capable of forming flocs, in which bacterial cells become self-flocculated by secreted extracellular polysaccharides and other biopolymers. The floc-forming bacteria play a central role in activated sludge, which has been widely utilized for the treatment of municipal sewage and industrial wastewater. Here, we use a floc-forming bacterium, Aquincola tertiaricarbonis RN12, as a model to explore the biosynthesis of extracellular polysaccharides and the regulation of floc formation. A large gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 74 publications
(87 reference statements)
1
21
0
Order By: Relevance
“…On the other hand, little EPS was extracted from the culture supernatants of the MMBΔ rpoN mutant, which is inconsistent with our previous finding that the transposon insertional rpoN1 (the rpoN ortholog) mutants of A. tertiarcarbonis RN12 released large amounts of exopolysaccharides into the culture broth (Yu et al ., ). This inconsistency may be due to the severe growth defect and pleiotropic effects caused by the deletion of the only rpoN gene in Z. resiniphila MMB while other three rpoN paralogs could somehow substitute for the cellular functions of rpoN1 in A. tertiarcarbonis RN12.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…On the other hand, little EPS was extracted from the culture supernatants of the MMBΔ rpoN mutant, which is inconsistent with our previous finding that the transposon insertional rpoN1 (the rpoN ortholog) mutants of A. tertiarcarbonis RN12 released large amounts of exopolysaccharides into the culture broth (Yu et al ., ). This inconsistency may be due to the severe growth defect and pleiotropic effects caused by the deletion of the only rpoN gene in Z. resiniphila MMB while other three rpoN paralogs could somehow substitute for the cellular functions of rpoN1 in A. tertiarcarbonis RN12.…”
Section: Resultsmentioning
confidence: 99%
“…Previously, we have demonstrated that the bound exopolysaccharides of wild‐type A. tertiaricarbonis RN12 strain and the released polysaccharides extracted from culture supernatants of the floc‐forming deficient rpoN1 mutant are highly similar in the monosaccharide composition and chemical structure (Yu et al ., ). Similarly, GC‐MS results showed that the bound EPS, extracted from the cell pellets of the wild‐type MMB strain, and released soluble EPS, extracted from culture supernatants of MMBΔ prsK and MMBΔ prsR mutants, were similarly composed of glucose, galactose and mannose (Supporting Information Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations